Estudio comparativo de venenos de ejemplares recien nacidos y adultos de Bothrops asper - Gutiérrez, José María (1980)
This paper is a comparative study of venoms of newborn and adult specimens of Bothrops asper from two Costa Rican populations: San Carlos, in the Atlantic versant and Puriscal in the Pacifico Comparison was on a basis of determination of the following effects: hemorrhage, myonecrosis, edema, proteolysis, hemolysis, and lethality, as well as neutralization of the lethal effect by polyvalent antivenom. Biochemical and immunochemical comparisons were done by mean s of electrophoresis, immunoelectrophoresis, and immunodiffusion. There are marked differences between newborn and adult venoms from both regions in electrophoretic and immunoelectrophoretic patterns, although the immunodiffusion plates showed an almost identical pattern. Venoms from newborn specimens are more proteolytic, hemorrhagic, edema-forming and lethal, whereas those of adult specimens are more hemolytic and induce a stronger myonecrotic action, characterized by a myolitic type of necrosis. Antivenom neutralizes the lethality of all venoms with similar ED50.Venoms of adult specimens from both regions showed a slight variation in the immunoelectrophoretic pattern, but a complete identity in immunodiffusion plates. Adult venoms from San Carlos are more hemorrhagic, and myonecrotic, whereas those of Puriscal are more proteolytic, having similar lethality, edema-forming activity, and hemolytic effect. The same differences were observed when venoms from newborn specimens from both populations were compared.